Evolution of resistance training in women: History and mechanisms for health and performance - Kraemer, W. J.; Fragala, M. S.; Ratamess, N. A. (Sports Medicine and Health Science, 2025)
Throughout history, cultural norms and stereotypes have discouraged resistance training in women. Today, as awareness and acceptance of resistance training in women has grown, supported by scientific research and advocacy, more women are achieving health and performance benefits from resistance training. This narrative review discusses the current scientific literature on sexual dimorphisms, the mechanisms underlying health and performance adaptations of resistance training in women, with implications for program design. In general, the physiological adaptations to resistance training in women are mediated largely by the neuroendocrine and immune systems, similar to in men albeit via some distinct predominant pathways involving sex hormones estrogen, testosterone, growth hormone (GH), and insulin-like growth factor- I (IGF-I). As a result, women may have unique adaptations in terms of muscle hypertrophy, substrate utilization, fatiguability, and recovery. Despite subtle physiological differences, women achieve measurable increases in strength, power and athletic performance via engaging in resistance training programs of sufficient frequency, intensity, and duration. Moreover, beyond performance, resistance training has a favorable impact on women's health including metabolic health, body composition, bone health, cardiovascular health, mental health, self-esteem, and body image. Resistance training recommendations for men and women are highly similar and goal-dependent, with some specific caveats that need to be addressed in women. As resistance training has become regarded as a key element of programs for achieving performance and health improvements in women, additional research may further our understanding.